2017
DOI: 10.1038/s41598-017-02023-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure Based docking studies towards exploring potential anti-androgen activity of selected phytochemicals against Prostate Cancer

Abstract: Prostate cancer (PCa) is the second most common malignancy amongst men worldwide. Under PCa maintenance therapy drugs acting as antagonists/partial agonists of hormone receptors against the prostate tissue are used in clinical practices. Prominent drugs being Cyproterone acetate, Flutamide, Bicalutamide, they not only cause acute and long-term toxicity, but also develops drug resistance among patients. Our focus has been on phytochemicals which do not exhibit any cytotoxicity and have significant androgen rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 36 publications
1
43
0
Order By: Relevance
“…Natural phytochemicals have attracted increasing attention in cancer therapy due to their broad anticancer activity and low cytotoxicity in normal cells (14,18). Genipin has demonstrated anticancer properties in different types of cancers such as hepatocellular carcinoma (15) and colon cancer cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…Natural phytochemicals have attracted increasing attention in cancer therapy due to their broad anticancer activity and low cytotoxicity in normal cells (14,18). Genipin has demonstrated anticancer properties in different types of cancers such as hepatocellular carcinoma (15) and colon cancer cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…Recent discoveries on plant phytochemicals against the PTP enzymes include Psidium guajava (Myrtaceae) leaf extracts which have one of the highest efficiency on the PTP enzyme active center inhibition to cure diabetes [63,64]. Natural plant phytochemicals such as curcumin as a ligand also showed high efficiency in binding with the active site of the PTP enzyme in prostate cancers through in silico docking analysis [65,66]. Compounds isolated from Sorbus commixta (Japanese flowering plant); lupeol and lupenone are also found to inhibit the PTP1B enzyme efficiently [67].…”
Section: Resultsmentioning
confidence: 99%
“…( 19 24 ) Recently, many have uncovered molecular targets of phytochemicals that directly mediate their biological and physiological functions. For example, Singh et al ( 25 ) conducted extensive screening of a total of 803 phytochemicals to examine their binding affinity for androgen receptor (AR) and found that the prenylated flavonoid isobavachin exhibited the highest affinity (–13.73 kcal/mol), followed by gabranin, athocyanin, and eiosemation. Also, β-secretase 1 (BACE1) has been noted to play a crucial role in development of Alzheimer’s disease.…”
Section: Biological Functions and Recently Identified Mechanismsmentioning
confidence: 99%